2018
DOI: 10.2337/db18-0903
|View full text |Cite
|
Sign up to set email alerts
|

Examining How the MAFB Transcription Factor Affects Islet β-Cell Function Postnatally

Abstract: The sustained expression of the MAFB transcription factor in human islet β-cells represents a distinct difference in mice. Moreover, mRNA expression of closely related and islet β-cell–enriched MAFA does not peak in humans until after 9 years of age. We show that the MAFA protein also is weakly produced within the juvenile human islet β-cell population and that MafB expression is postnatally restricted in mouse β-cells by de novo DNA methylation. To gain insight into how MAFB affects human β-cells, we develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 51 publications
(87 reference statements)
7
60
0
Order By: Relevance
“…It is also likely that the human MAFA S64F :MAFB heterodimeric activator will impart a unique influence on β cells compared to the mouse MafA S64F :MafA homodimeric activator (Cyphert et al, 2019;Hang and Stein, 2011), which may explain why neuroendocrine tumors and overt hypoglycemia was not observed in aged MafA S64F/+ mice (data not shown). Notably, MAFB was recently shown to be essential for the formation of human embryonic derived β cells and insulin production (Russell, 2020), whereas there is no phenotype associated with the loss of MafB in mouse islet β cells (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also likely that the human MAFA S64F :MAFB heterodimeric activator will impart a unique influence on β cells compared to the mouse MafA S64F :MafA homodimeric activator (Cyphert et al, 2019;Hang and Stein, 2011), which may explain why neuroendocrine tumors and overt hypoglycemia was not observed in aged MafA S64F/+ mice (data not shown). Notably, MAFB was recently shown to be essential for the formation of human embryonic derived β cells and insulin production (Russell, 2020), whereas there is no phenotype associated with the loss of MafB in mouse islet β cells (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…(Raum et al, 2006;Raum et al, 2010) Expression of the other large Maf family member produced in the islet, MafB, differs from MafA in being expressed in both murine aand β-cells developmentally (Cyphert et al, 2019;Hang and Stein, 2011), then postnatally only in a cells and a subpopulation of β cells during pregnancy (Banerjee et al, 2016;Cyphert et al, 2019). Moreover, genetic studies have demonstrated that MafB is dispensable in regulating adult murine islet β cell function, except during pregnancy (Banerjee et al, 2016;Cyphert et al, 2019). MafA expression during mouse β cell development compensates for the absence of MafB, although glucagon secretion from islet a cells is compromised (Cyphert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, due to inherent sensitivity issues related to performing proteomics on encapsulated samples, we were unable to confirm ARX or MAFB decrease as a consequence of MECP2 activation in the transplanted cells. Of note, as MAFB retains its expression in mature human β-cells (Conrad et al, 2016;Cyphert et al, 2019), it is possible that its regulation is not affected in the human context. Interestingly, MECP2 was organically networked with regulated proteins involved in the lipid and energy metabolism (Figure 3F), suggesting a link between the improved energetic status of the transplanted cells and its upregulation.…”
Section: Improved Energy Metabolism Status Is Linked To Enhanced Exprmentioning
confidence: 99%